PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU CORPORATE INTERNET REPORTING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Charellin Vita Miranda, 12.05.52.0243; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of leverage, liquidity, company size and profitability of the timeliness corporat Internet Reporting. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period of 2013 to 2015. The technique used is purposive sampling, the sample of 102 observation data from 34 companies that meet the criteria for the research sample. Statistical analysis was performed using multiple linear regression and hypothesis testing. Based on the results of data analysis can be concluded; There is a significant negative influence and leverage the timeliness Corporate Internet Reporting, No significant effect of liquidity on the timeliness Corporate Internet Reporting, there is a negative and significant impact on the company size timeliness Corporate Internet Reporting, There is no effect of profitability on the timeliness of the Internet Corporate Reporting.  Keywords: Leverage, Liquidity, Company Size, Profitability, Timeliness Corporate Internet Reporting